Successful Lung Transplantation From Hepatitis C Positive Donor to Seronegative Recipient. Issue 4 (16th January 2017) - Khan, B.; Singer, L. G.; Lilly, L. B.; Chaparro, C.; Martinu, T.; Juvet, S.; Pipkin, M.; Waddell, T. K.; Keshavjee, S.; Humar, A.; Cypel, M.
Abstract : Lung transplantation using RNA+ hepatitis C (HCV+) donors to seronegative recipients is not currently performed due to the very high risk of transmission. Previous reports have shown poor survival when this practice was applied. The emergence of new direct‐acting antiviral drugs (DAA) suggests a high chance of sustained virologic response in immunocompetent patients. We report here successful transplantation of lungs from HCV+ donor to HCV− recipient. The recipient was an HCV− patient with chronic lung allograft dysfunction. Viral transmission occurred early posttransplant but excellent clinical outcomes were observed including elimination of HCV after 12 weeks of treatment using DAAs. Abstract : The authors demonstrate successful outcomes of intentional lung transplantation using a hepatitis C (HCV)‐positive donor to a HCV‐negative recipient treated with a direct antiviral agent 6 weeks after transplantation.